O DIREITO FUNDAMENTAL À MORADIA E AS POLÍTICAS HABITACIONAIS NO BRASIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The article aims to study the fundamental and social right to decent housing and public housing policies implemented in Brazil. The disorderly growth of Brazilian urban centers, intensified by the growing rural exodus in the twentieth century, imposed on the Government the adoption of policies and measures to minimize the negative social, economic and legal effects of irregular occupation of urban land. In fact, the right to decent housing is an expression of the dignity of the human person and is intrinsically related to the realization of the social function of property. The evolution of property rights culminated in the abandonment of an egotistical and individualistic conception to assign contours of sociality to this first-generation right. Thus, the State's performance in the various public housing policies had (or should have) as a substantial concern the fulfillment of the social function of property and the protection of the right to housing. The evolution of these policies culminated in the edition of regulations of land regularization, which is shown as the most viable current political option to minimize the harmful effects of the state omission in the occupation of Brazilian urban centers. The novel law of land regularization n. 13,465/17 created important legal institutes that deserve special attention from legal practitioners.